Conversational Strategies Used by Women Speakers in Same-Sex Communication: A Research on Noor Tagouri Podcast - Deadora Rahma Muthia; Didin Nuruddin Hidayat; Alek Alek (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This article sought to explore women's language style through a regular conversation in a natural setting conducted by women speakers. Considering the potential of Podcast on Spotify as a means to gather the conversation discourse, the writers were fascinated by one of the Podcasts performed by an American journalist and activist named Noor Tagouri. She initiated and ran a program called The Process to disclose someone's struggle, unique costumes, and way of thinking behind his/her success. This Podcast was chosen in terms of personal and introspective topics developed by Tagouri and her guest, Lisa Ling, whose profession was also a journalist. Through personal and introspective ideas, the writers were able to identify women's linguistic features such as: minimal responses, hedges, tag questions, questions, commands and directives, swearing and taboo language, and compliments in order to build a cooperative environment. This article employed descriptive qualitative methods following the procedures proposed by Creswell   (2014): collecting the data, analyzing the data, and interpreting the data. From thirty-four minutes of conversation, the result indicated that the speakers frequently used the features of hedges (55%). Then, followed by Minimal response occurred (20%), questions (12%), compliment (8%), tag questions (5%), and commands, directives, swearing and taboos (0%). It can be concluded that the use of hedges was more widely used to maintain the flow of conversations which in line with turn-taking, courtesy, and mitigating miscommunication between speakers.